Monte Carlo Analysis For Prediction Of Noise From A Construction Site - Haron, Zaiton; Yahya, Khairulzan (Penerbit Universiti Sains Malaysia, 2009)
The large number of operations involving noisy machinery associated with construction site activities result in considerable variation in the noise levels experienced at receiver locations. This paper suggests an approach to predict noise levels generated from a site by using a Monte Carlo approach. This approach enables the determination of details regarding the statistical uncertainties associated with noise level predictions or temporal distributions. This technique could provide the basis for a generalised prediction technique and a simple noise management tool